Virtual factory model development for AI-driven optimization in manufacturing - Tõnis Raamets; Kristo Karjust; Aigar Hermaste; Karolin Kelpman (Proceedings of the Estonian Academy of Sciences)
This paper examines the development of a virtual factory model to optimize overall equipment effectiveness (OEE) in a planned manufacturing facility. Using digital simulations based on a wood manufacturing setup, AI-driven models can be applied to analyze specific OEE metrics, allowing for targeted identification of production bottlenecks and efficiency improvements. The virtual factory enabled scenario testing for the proposed facility, providing actionable insights without impacting current operations. The preliminary results indicate that AI integration within a virtual factory can significantly enhance planning and decision-making for future production investments.